Educação domiciliar no Brasil : trajetória e organização a partir de 1990 - Pessoa, Mayara Lustosa Silva (2019)
The practice known as home education or homeschooling has been evident in the Brazilian public scene. The theme has strong implications for the educational debate, appearing as a solution for some or as a concern for others, while opposing the school institution and questioning public educational policies. In view of this, this study aimed to analyze the socio-historical trajectory and the ways of organizing the mobilization in favor of this modality in Brazil, from 1990. Given the nature of the object, it was adopted the qualitative and descriptive research, using different sources of information: a) bibliographic research, as the main base; b) document analysis as a complementary source and c) empirical research with the National Association of Home Education (ANED), using semi-structured interviews. The approach with ANED had a privileged space, given that this is the main representative entity of the mobilization in the country and took place with the purpose of knowing the history, organizational characteristics, objectives and strategies of the association. It can be seen that neoliberalism is one of the most determining theoretical bases of home education and that it finds its main influence in the middle class. Thus, it becomes increasingly linked to conservative guidelines, such as the School Without Party program, although the growing mobilization for the regulation of the modality can be analyzed from different interpretative standards, depending on the theoretical perspective that is used. The results reveal a fruitful discussion and point to an international mobilization that has history, collective project and organizational strength that shows no signs of cooling, in spite of the current unfavorable legal conditions